Auditory Hallucination and Bipolar Disorder in a Mental Rehabilitation Patient: Case Study - Permana, Gin Gin Sugih; Daniati, Eva; Riansyah, Alvi (Nursing Case Insight Journal, 2025)
Mental health is a condition in which individuals can develop physically, mentally, spiritually, and socially so that they are able to realise their potential, overcome stress, work productively, and contribute to society. This research was conducted at the Nur Ilahie Assanie Mental Rehabilitation Clinic Samarang, Garut Regency. The purpose of this study was to gain more real experience in carrying out the process of mental nursing care with hallucinatory sensory perception disorders focusing on improving the client's perceptual power and the client can relate to reality which includes assessment, diagnosis formulation, planning, implementation and evaluation. This case shows a holistic approach (biopsychosocial-spiritual) is effective in dealing with cases of hallucinations in bipolar disorder. Structured and sustainable nursing interventions are proven to reduce hallucination symptoms. In addition, the role of family has a significant influence in the long-term rehabilitation process. On the other hand, medication compliance is also a key factor in controlling symptoms and preventing relapse. Thus, a combination of medical therapy, family support, and a comprehensive approach from healthcare professionals is essential in the management of bipolar disorders with hallucinatory symptoms.